Big Data and Personal Data Between the Principles of Protection and Innovation - Zolynski, Célia (Law, State and Telecommunications Review, 2020)
Objective ”“ The article contrasts the problem of Big Data with the possibilities and limits of personal data protection. It is an original contribution to the academic discussion about the regulation of the Internet and the management of algorithms, focusing on Big Data. Methodology/approach/design ”“ The article provides bibliographic research on the opposition between Big Data and personal data protection, focusing on European Union law and French law. From the research is possible to identify regulatory alternatives do Big Data, whether legal-administrative nature or technological nature. Findings ”“ The article enlightens that, in addition to the traditional regulatory options, based on the law, there are technological options for regulating Big Data and algorithms. The article goes through an analysis of administrative performance, such as France’s CNIL (Commission nationale informatique et libertés, CNIL), to show that it has limits. Thus, the article concludes that there is a need to build a new type of regulation, one that is open to the inputs of regulated parties and civil society, in the form of new co-regulatory arrangements. Practical implications ”“ The article has an obvious application since the production of legal solutions for Internet regulation requires combining them with technological solutions. Brazil and several Latin American countries are experiencing this agenda, as they are building institutions and solutions to solve the dilemma of personal data protection. Originality/value ”“ The article clarifies several parts of the General Data Protection Regulation (EU Regulation 2016/679) and its applicability to Big Data. These new types of data processing impose several legal and regulatory challenges, whose solutions cannot be trivial and will rely on new theories and practices.